(untitled) (Ustozlar uchun, 2025)
Bilingual students, possessing linguistic and cognitive advantages derived from their multilingualism, present unique opportunities and challenges in the English language classroom. This article explores the nuanced landscape of teaching English to these learners, moving beyond a "one-size-fits-all" approach to emphasize the importance of leveraging their existing linguistic resources, cultural backgrounds, and individual learning profiles. The paper synthesizes research on effective pedagogical practices, including translanguaging, code-switching, culturally responsive teaching, and differentiated instruction, demonstrating how these strategies can create a supportive and inclusive learning environment where bilingual students can thrive. By providing a framework for understanding bilingualism and offering practical guidance for educators, this article aims to equip teachers with the knowledge and tools to effectively support bilingual students in their journey toward English language proficiency and academic success while honoring their linguistic identities.